Sequenciamento da produção e despacho de caminhões em plantas de concreto - Mateus Vilela Souza (2016)
The demand for high quality concrete and a Just-In-Time policy in modern constructions have been changing the concrete market lately, mainly in countries with big potentials of economic growth like Brazil, India and China. The RMC (Ready Mixed Concrete) has had a great deal of market penetration because of its quality guarantee and large supply flexibility. It allows the supply of large quantities in a short time. The RMC is produced in plants and transported by specialized vehicles to meet the demands of a set of constructions. Production planning and how the demands will be met are mostly performed by experienced employees. And, in general, they are elaborated without the use of a tool that assists them in the best possible solution. In this context, we make a large literature review and propose a new approach to the scheduling production and distribution of RMC problem, considering that the plants can meet each demand alone or together. We also generate a set of instances, propose a Mixed-Integer Linear Programming model and a randomic constructive heuristic to solve this problem. The best approach is utilizing the model started with a solution from the heuristic.